Modern Architecture in Teófilo Rego Archive - TREVISAN, Alexandra (2015)
The Project Photography and Modern Architecture and “School of Oporto”: interpretations on Teófilo Rego archive carried out for the last two years, has already accomplished the majority of the proposed goals, and created, in simultaneous, a theoretical corpus grounded on a consistent research that permits to share some reflections and conclusions within an enlarged international context. This paper intends to systematize the work carried out within this project, departing from three fundamental aspects: 1. The commercial archive of the photographer, where we gathered the images. This archive provided the main sources of theoretical development, namely in what concerns to it's articulation with Portuguese modern architecture and the “School of OPorto”. It was also this achive that enabled the construction of an online database. 2. The revelation of less known or even simply unknown architects, never referred works, and subjects incipiently treated, present in the Teófilo Rego archive. This documentation generated some new research line, who initially were not previewed. 3. The creation of alternative and grounded hypothesis for new approaches to the history of modern architecture produced in Portugal, departing from monographic approaches or transversal subjects in the chronological period in study, from 1940 to 1970.